A precarização do trabalho e das políticas sociais na sociedade capitalista: fundamentos da precarização do trabalho do assistente social - Cavalcante, Girlene Maria Mátis (2009)
A dissertation submitted to the Graduate Program in Social Service of UFAL (Federal University of Alagoas) is the object of study the instability of employment and social policies in capitalist society, as historical and theoretical foundations of the precariousness of the work of social. The research aimed to investigate the elements that define the current precariousness of the work of social worker, seeking to link with the instability of employment and social policies in the present. The research methodology involved the bibliographic and documentary procedures. The literature search allowed the theoretical development, through the reading of reports, articles and works on the subject, using fichamentos and summaries of relevant content for search. The desk research has examined labor legislation and articles of the Constitution which regulate labor relations, and consider the data accumulated on the labor market of Social Service. The study examined the economic policy, social policy and labor market maintain a constant and professional relationship, with reciprocal trade between them. In this sense, social policy is subordinated to economic policy, and that interferes with the quality of public services that are provided to the population and reflects the working conditions of professionals engaged in the social area. In turn, the work of professionals engaged in social services is also marked by the process of change at work.